Industrial Competitiveness Cost Reduction - Halevi, Gideon. (Springer Netherlands : Imprint: Springer, 2006)
The objectives of industrial management are: - Implementation of the policy adopted by the owners or the board of directors - Optimum return on investment - Efficient utilization of Men, Machine and Money. In other words, industry must make profit. Manufacturing represents only one aspect of the activities of industrial management. Present-day manufacturing methodology does not consider making profit as their primary objective. The manufacturing process requires the knowledge of many disciplines, such as design, process planning, costing, marketing, sales, customer relations, costing, purchasing, bookkeeping, inventory control, material handling, shipping, and so on. Each discipline considers the problem at hand from a different angle. For example, in the case of the introduction of a new product: - Marketing will evaluate its attractiveness to the customers -The product designer will evaluate methods of achieving product functions - The process planner will evaluate the required resources - Finance will evaluate the required investment - Manpower will consider the work force demands -The manufacturing engineer will consider floor space and material handling - Purchasing and shipping will consider how to store the product x Preface Each discipline optimizes its task to the best of its ability. Each manufacturing discipline has its own objectives and criteria of optimization according to its function. For example: the designer main objective is meeting product specifications; the process planner’s main objective is that the items will meet drawing specifications; the production planner’s main objectives are meeting the due date, and minimizing work-in-process.